Limnological aspects of Loch Logan, an urban impoundment - Vos, Adriana Tascha (University of the Free State, 2002)
At present many water resources in South Africa are polluted by industrial effluents, domestic and commercial sewage, agricultural runoff and litter. Declining water quality, associated with human activities, has created environmental and public health problems. Loch Logan is an urban impoundment near the city centre of Bloemfontein, Free State, South Africa, which is fed through Bloemspruit, a canal, which collects stormwater runoff. The catchment area is -16 x 106 m2 and after a rainstorm ±30 % of the rain ends as runoff water in Loch Logan. The study was conducted between January 2000 and May 2001 to determine among others the seasonal and diel variation patterns of limnological characteristics, i.e. physical, chemical and biological parameters, to contribute to the limnological knowledge for proper management and conservation of the system. The physico-chemical characteristics of Loch Logan showed a distinctive seasonal trend, which was primarily influenced by climate and rainfall. Discharge has been proven to be an important variable influencing the water quality of Loch Logan. After a rainstorm the nutrient concentrations increased in Loch Logan, as well as the turbidity, but the conductivity decreased. All the data collected showed that Loch Logan is an eutrophic system with an average reactive ortho-phosphate (PO4-P) concentration of 78.7 µg/l and a maximum of 648.3 µg/l.The average and maximum nitrogen concentrations were also high: ammonium nitrogen (NH4-N) 181.5 µg/l and 1,032.6 µg/l,respectively, and nitrate nitrogen (N03-N) 201.2 µg/l and 1,375.1 µg/l respectively. The pollution sources, organic and inorganic, are mainly stormwater runoff, garden and domestic trash and also human sewage. During the decomposition of these pollutants the oxygen (02) concentration decreased drastically, especially in the bottom water layer where the oxygen concentration was usually low. The average oxygen concentration in the surface water was high at 6.6 mg/l (72.8 %) compared to the average of 2.0 mg/l (16.5 %) in the bottom layer. The annual average chlorophyll-a concentration in Loch Logan (average 56.8 µg/l and maximum 487.2 µg/l) was typically that of a eutrophic system (15-75 µg/l). Eutrophication is therefore seen as the single most important threat to the water quality of the Loch Logan aquatic system. A higher average in Chl-a concentration was found during the summer than during the winter. Some of the dominant algal species (Chlamydomonas; Chlorella, Euglena, Scenedesmus) are indicators of polluted water and the algae also shown seasonal trends. During blooms the algal composition mainly consists of cyanobacteria, namely Microcystis sp. (dominating) and Anabaena sp. In the diel variations there was no distinctive patterns in the physico-chemical characteristics, except for temperature, oxygen and pH. The photosynthesis rate per chlorophyll-a was higher in October (3.68 mgC/mgChl-a/h) than in July (1.24 mgC/mgChl-a/h), which indicated that temperature was one of the controlling factors of photosynthesis. Various management and restoration options for Loch Logan were discussed, for example diversion of stormwater, diluting, flushing and phosphorus inactivation. The solution for the pollution is possibly a combination of the options mentioned above.

Huidiglik is baie van Suid-Afrika se waterbronne besoedel deur industriële uitvloeisels, huishoudelike- en besigheidsriool, landbou afloop en rommel. Verlaging in waterkwaliteit wat met menslike aktiwiteite geassosieer word, veroorsaak omgewings en publieke gesondheidsprobleme. Loch Logan is enstedelike dam naby die middestad van Bloemfontein, Vrystaat, Suid-Afrika, wat gevoed word deur Bloemspruit, en kanaal, wat stormwater afloop versamel. Die opvangsgebied is -16 x 106 m2 en na enreënstorm eindig ±30 % van die reën in Loch Logan as afloopwater. Die studie is vanaf Januarie 2000 tot Mei 2001 uitgevoer en onder andere is die seisonale en daaglikse veranderingspatrone van limnologiese eienskappe, byvoorbeeld fisiese-, chemies- en biologieseparameters, bepaal sodat bydraes tot die limnologiese kennis gemaak kan word vir bestuur en bewaring van die stelsel. Die fisies-chemiese eienskappe van Loch Logan wys duidelike seisonale neigings wat hoofsaaklik deur die klimaat en reënval beïnvloed is. Dit is bewys dat afloopwater en belangrike invloed op Loch Logan se waterkwaliteit het. Na en reënstorm het die voedingstofkonsentrasies in Loch Logan verhoog asook die troebelheid, maar die geleiding het verlaag. AI die data wat versamel is, dui daarop dat Loch Logan en eutrofiese stelsel is met en gemiddelde reaktiewe orio-fosfaat (PO4-P) konsentrasie van 78.7 µg/l en enmaksimum van 648.3 µg/l. Die gemiddelde en maksimum stikstof konsentraties was ook hoog: ammonium stikstof (NH4-N) was onderskeidelik 181.5 µg/l en 1,032.6 µg/l, en nitraat stikstof (N03-N) was onderskeidelik 201.2 µg/l en 1,375.1 µg/l Die besoedelingsbronne, organies en anorganies, is hoofsaaklik stormwater afloop, tuin- en huishoudelike afval asook menslike riool. Tydens die afbreek van die besoedelingstowwe het die suurstof (02) konsentrasie drasties gedaal, veral in die bodemlaag waar die suurstof konsentrasie meestal baie laag was. Die gemiddelde suurstof konsentrasie in die oppervlak water was 6.6 mg/l (72.8 %) in vergelyking met die gemiddeld van 2.0 mg/l (16.5 %) in die bodemlaag. Die jaarlikse gemiddelde chlorofil-a konsentrasie in Loch Logan (gemiddeld 56.8 µg/l en maksimum 487.2 1-191I)was tipies dié van 'n eutrofiese stelsel (15-75 µg/l). Eutrofikasie word dus gesien as die enkel mees belangrikste bedreiging vir die waterkwaliteit van Loch Logan se akwatiese stelsel. 'n Hoër gemiddeld in Chl-a konsentrasie is gedurende die somer gevind as gedurende die winter. Van die dominante algspesies (Chlamydomonas, Ch/orel/a, Euglena, Scenedesmus) is aanduiders van besoedelde water en die alge toon ook 'n seisonale neiging. Die algsamestelling tydens die opbloeie het meestal uit die sianobakterieë, naamlik Microcystis sp. (dominant) en Anabaena sp. bestaan. Tydens die daaglikse veranderinge is daar geen duidelike patrone van die fisieschemiese eienskappe waargeneem nie, behalwe vir temperatuur, suurstof en pH. Die fotosintese tempo per chlorofil-a was hoër tydens Oktober (3.68 mgC/mChl-a/h) as tydens Julie (1.24 mgC/mChl-a/h), wat 'n aanduiding is dat temperatuur een van die beheerende faktore van fotosintese was. Verskeie bestuur en restorasie keuses vir Loch Logan is bespreek, byvoorbeeld omleiding van stormwater, verdunning, spoeling en fosfaat inaktivering. Die oplossing vir die bekamping van besoedeling is waarskynlik 'n kombinasie van bogenoemde aksies.
Dissertation (M.Sc. (Plant Sciences))--University of the Free State, 2002
Keywords: Urban impoundment; Eutrophication; Physical and chemical parameters; Nutrients; Seasonal cycles; Diel changes; Algae; Blooms and management; Lake ecology -- South Africa -- Bloemfontein; Surface impoundments -- Environmental aspects -- South Africa -- Bloemfontein; Water resources management